Nutrition and arthritis - Rayman, Margaret; Callaghan, Alison; Wiley InterScience (Online service) (Oxford ; Ames, Iowa : Blackwell Pub., 2006)
Arthritis affects millions of people throughout the world and while its treatment is usually medical or surgical, there exists an increasingly large body of evidence concerning the positive effects of nutrition on the condition. There are over two hundred forms of rheumatoid disease, with conditions varying in prevalence. In this important title the authors have focussed on osteoarthritis (OA) and rheumatoid arthritis (RA), the most common arthritic diseases with the largest body of dietary data. Including coverage of disease incidence and prevalence, pathology, aetiology and measures of disease assessment and dietary risk factors,'Nutrition and Arthritis' is a clear, concise and user-friendly book gathering the latest research to bring the reader state-of-the-art information on: Micronutrients (e.g. vitamins C, D and selenium), food supplements and their potential to ameliorate arthritis, Polyunsaturated fatty acids, with particular attention paid to n-3 fatty acids Glucosamine and chondroitin, the value of exclusion, vegetarian, vegan and other dietary approaches.; Nutritionists and dietitians, including those working in the health services, rheumatologists, orthopaedic surgeons, general practitioners, osteopaths and commercial organisations involved in the formulation of dietary supplements will find this book an important and practical reference source. Libraries in medical schools and universities and research establishments where nutrition, dietetics and food science are studied and taught will find it a valuable addition to their shelves.
Introduction -- Classification, Pathology and Measures of Disease Assessment -- Aetiology and Risk Factors for Osteoarthritis and Rheumatoid Arthritis -- Current Management of Osteoarthritis and Rheumatoid Arthritis -- Nutritional Status and Adequacy of the Diet in Rheumatoid Arthritis and Osteoarthritis -- Popular Dietary Approaches -- Exclusion, Vegetarian, Vegan and Other Dietary Approaches in Rheumatoid Arthritis -- Role of Micronutrients in the Amelioration of Rheumatoid Arthritis and Osteoarthritis -- Polyunsaturated Fatty Acids in the Treatment of Arthritis -- Glucosamine and Chondroitin in Osteoarthritis -- Other Foods or Supplements Marketed for Arthritis Relief -- Assessment of Level of Evidence for Nutritional Recommendations and Suggestions for the Future -- Appendix 1: How to Interpret the Statistical Data on Studies Quoted in this Book -- Appendix 2: Malnutrition Universal Screening Tool -- Appendix 3: Table of UK and USA Dietary Reference Values for Vitamins, Minerals and Trace Elements -- Appendix 4: Elimination Diet for Rheumatoid Arthritis.
Includes bibliographical references and index.
Print version record.
Keywords: Arthritis -- Nutritional aspects; Arthritis -- Diet therapy; Electronic books